Relationship between evil and thinking activities - Hutabarat, Franklin; Reymand Hutabarat, (Technium Social Sciences Journal, 2020)
Hannah Arendt argued that evil is all too frequently the product of normal citizens following the principles and prescriptions of a morally corrupt government. However, is it acceptable to blame the public organizing structure of the state or the bureaucracy as the source of rampant corruption? Through a documentary analysis based on the systematic examination and review of key sources published in various sources, it may conclude that corruption is a form of banal crime after Arendt's line of thought about the banality of crime, since the individuals involved are unable to think objectively and judge in a reflective and representative way. They blindly follow the orders of superiors and the old corrupt laws or the method of work.